Politeness Shifts in Self-Translation: A Case Study of Umera Ahmad’s ‘La Hasil’ (Journal of Asian Development Studies, 2025)
The study aims to explore the politeness strategies in the novel of Umera Ahmad ‘La Hasil.’ The purpose of the study is to find out the politeness strategies in Urdu text of the novel and then it’s translation in the English version of the novel entitled as ‘Hollow Pursuits.’ The objective of the study is to highlight the politeness strategies and its types in the utterances of the characters as well as in the narration. In order to evaluate the category of each and every example, the theory of Brown and Levinson (1987) is adopted along with the framework of Translation Techniques of Molina and Albir (2002). For this study, the manual method was adopted along with AntConc. The study adopts qualitative research method. For the purpose of data collection the manual method was adopted and twelve dialogues were selected with the distribution of three for each category. The data was analyzed on the basis of the theory and its types and linguistic markers for these specific categories. The study concludes that most of the translation strategies carry the level of equivalence (dynamic and formal) as formal equivalence carried examples with the number of 7, 8, 9, 12 in the study, whereas the remaining  illustrations fall under  dynamic equivalence. Thus the study provides direction for future researchers to explore politeness strategies in all the chapters sequentially and more work can be done on the comparative analysis of politeness strategies across various cultures in the domain of translation studies.